A randomized, double blind, standard controlled trial to compare safety and efficacy of two leading brands of Ashwagandha products in patients suffering from mental health related symptoms - Limaye, Dnyanesh; Neogi, Ayan; Kondepudi, Karthik; Mandlik, Sagar (International Journal of Research in Medical Sciences, 2024)
Background: Mental health related symptoms are common among the population. Current treatment exhibits serious adverse effects, delayed onset of action and low efficacy. Ashwagandha has a variety of beneficial effects in mental health disorders. We did a comparison of two Ashwagandha brands using a variety of scales for anxiety, depression, stress, and sleep quality. Methods: The study was conducted in 80 patients suffering from mental health related symptoms. Test product used was: Herbochem +91 Ashwagandha 500 mg capsules and control used was: KSM 66 Ashwagandha 600 mg capsules. Results: The reduction in the perceived stress scores and Hamilton depression scale scores at day 30/60 from day 0 was higher in the test group as compared with the control group. The reduction in the Beck’s anxiety inventory scores at day 30/60/90 from day 0 was higher in the test group as compared with the control group. The increase in the Pittsburgh sleep quality index scores at day 30/60 from day 0 was higher in the test group as compared with the control group. The reduction in the serum cortisol scores at day 30 from day 0 was higher in the test group as compared with the control group. Results showed that, the incidence of adverse events was same in both groups. Conclusions: It is important to note that test product having 500 mg Ashwagandha, showed better efficacy as compared to control product having 100 mg more (600 mg) of Ashwagandha.